2023
DOI: 10.21203/rs.3.rs-2448437/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tbx6/Ripply mechanism as dynamic-to-static converter in somite segmentation

Abstract: The metameric pattern of somites is created based on oscillatory expression of clock genes in presomitic mesoderm. However, the mechanism for converting the dynamic oscillation to a static pattern of somites is still unclear. Here, we provide evidence that Ripply/Tbx6 machinery is a key regulator of this conversion. Somite boundary determination by Ripply1/Ripply2-mediated removal of Tbx6 protein leads to cessation of clock gene expression in zebrafish embryos. On the other hand, activation of ripply1/ripply2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Goto [52] further demonstrated that the castle is represented on an enlarged scale, as other studies have pointed out. Yabe [53] visualized the distortions in the Takada Shoho Castle Map using quantitative methods, but did not use a local regression; as discussed later in the Methods section, only a global regression was used. Therefore, the local distortions were not accurately visualized.…”
Section: Distortion Of the Shoho Castle Mapsmentioning
confidence: 99%
“…Goto [52] further demonstrated that the castle is represented on an enlarged scale, as other studies have pointed out. Yabe [53] visualized the distortions in the Takada Shoho Castle Map using quantitative methods, but did not use a local regression; as discussed later in the Methods section, only a global regression was used. Therefore, the local distortions were not accurately visualized.…”
Section: Distortion Of the Shoho Castle Mapsmentioning
confidence: 99%